2019
DOI: 10.2217/fvl-2019-0047
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1 rs1800469 Gene Polymorphism in the Development of Cirrhosis & Hepatocellular Carcinoma in Pakistani HCV Patients

Abstract: Hepatocellular carcinoma (HCC) has been increasing among Pakistani males. Aim: The main objective of this study was to evaluate the role of TGF-β-1 gene polymorphism as a risk factor in chronic hepatitis C virus (HCV) infected HCC patients in Pakistan. Patients & methods: A total of 286 subjects were recruited into three different groups (Group I: 96 healthy controls, Group II: 96 HCV, Group III: 94 HCC). Results: A significant increase in genotype and allele frequencies of TGF-β-1 gene was observed in HCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Several studies reported an association between allele T of TGF-β -509 C/T and higher fibrosis stages with an increase in cytokine expression [ 61 , 62 , 63 ]. Our research found a statistically significant association between the CC genotype and higher fibrosis stages, as shown in Table 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported an association between allele T of TGF-β -509 C/T and higher fibrosis stages with an increase in cytokine expression [ 61 , 62 , 63 ]. Our research found a statistically significant association between the CC genotype and higher fibrosis stages, as shown in Table 7 .…”
Section: Discussionmentioning
confidence: 99%